Dependence of cytokinemia on the clinical course of chronic obstructive pulmonary disease combined with hypertension. - Kapustnyk, V.A A.; Kostyuk, I. F.; Melenevych, A. Ya. (Medicni Perspektivi, 2018)
Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous disease. The prevalence of COPD continues to increase steadily. 90% of patients with COPD have at least one comorbid pathology. Among concomitant COPD diseases pathologies of the cardiovascular system prevail. The variety of the disease course in patients is the basis for distinguishing COPD patients with similar pathophysiological mechanisms based on analysis of biomarkers. The aim of the study was to analyze the dependence of cytokinemia (interleukin-18 and interleukin-10) on the clinical course of the disease in patients with COPD in combination with hypertension (HT). In total, 100 occupational COPD (GOLD 2, group B) patients in remission were monitored. The main group included 69 patients with COPD in combination with HT stage II, the comparison group - 31 patients with isolated COPD, and the control group - 20 healthy volunteers. All groups were comparable by sex and age. Levels of interleukin-18 (IL-18) and interleukin-10 (IL-10) were significantly higher in COPD patients combined with HT compared to healthy volunteers and isolated COPD. Growth of IL-18/IL-10 ratio is associated with increase in the degree of dyspnea, decrease in exercise tolerance, increase in desaturation during the 6-min walk test, decrease in body mass index, waist and mid-upper arm circumferences, and also more frequent detection of emphysematous changes in chest X-ray. Thus, the IL-18/IL-10 ratio reflects the state of the immune-inflammatory process and has the potential to predict the future risk of developing irreversible pathological changes in the respiratory tract, alveoli and lung vessels with the formation of emphysematous and fibrotic changes.